Strengthening Supervision Government Internal Control System (SPIP) at The General Election Commission East Kalimantan Province - Amaliah An Nuur; Daryono Daryono (Iapa Proceedings Conference, 2021)
The purpose of this research is to know and understand specifically about the implementation of bureaucratic reform through the Grand Design 8 Bureaucratic Road Map, one of which will be examined, namely Strengthening Supervision through a form of system application called the Government Internal Control System ( SPIP) with its implementation at the Provincial General Electi on Commission Secretariat. East Kalimantan. This research was conducted to determine the extent to which this control system was successfully implemented at the General Election Commission of East Kalimantan Province with the technical implementation by the Government Internal Control System Task Force Team with a comprehensive assessment covering Gratification, Public Complaints, Conflicts of Interest, Integrity Zones, and SPIP itself. Research Methodology in the form of Qualitative Creswell using Phenom enological Data Analysis in the form of an understanding of experience about phenomena, the existence of philosophy and sociology, and interviewing informants as the owner of research sources who will provide statements, meanings, and general descriptions of experiences. The number of informants in the study was 14 (fourteen) people consisting of 13 (thirteen) people from the General Election Commission of East Kalimantan Province and 1 (one) person from the Inspectorate General of the General Elections Commission of the Republic of Indonesia.